2022
DOI: 10.3389/fpls.2022.824781
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Methyl Jasmonate in Gene Expression, and in Hormonal and Phenolic Profiles of Holm Oak Embryogenic Lines Before and After Infection With Phytophthora cinnamomi

Abstract: The dieback syndrome affecting Quercus ilex and other oak species impels the search for tolerant plant genotypes, as well as methods of plant immunization against such infections. Elicitation treatments can be an effective strategy to activate plant defense response and embryogenic lines represent a promising tool to generate new tolerant genotypes and also to study early markers involved in defense response. The aim of the presented work was to investigate changes in gene expression, and in hormonal and pheno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 64 publications
(82 reference statements)
1
3
0
Order By: Relevance
“…When the tissues of selected lines inhibit the growth of a mycelium, the explanation may lie in their production of externally exported resistance compounds. Dual culture assays have confirmed the chemotactic attraction of P. cinnamomi mycelia toward holm oak somatic embryos to be dependent on the latter's genotype [15,16]. The same has also been observed in vitro with shoots and leaves [13] and in roots during the infection process in vivo [39].…”
Section: Introductionsupporting
confidence: 56%
See 1 more Smart Citation
“…When the tissues of selected lines inhibit the growth of a mycelium, the explanation may lie in their production of externally exported resistance compounds. Dual culture assays have confirmed the chemotactic attraction of P. cinnamomi mycelia toward holm oak somatic embryos to be dependent on the latter's genotype [15,16]. The same has also been observed in vitro with shoots and leaves [13] and in roots during the infection process in vivo [39].…”
Section: Introductionsupporting
confidence: 56%
“…The genetic transformation of somatic embryos using a Gnk2-like protein may also allow genotypes with improved anti-oomycete activity to be obtained [14]. The induction of epigenetic changes on somatic embryos elicits a defense response and provides another opportunity to obtain tolerant holm oak trees [15,16]. There is increasing evidence that following exposure to an environmental stimulus, different genotypes acquire some kind of epigenetic memory that determines new behavior when restimulated.…”
Section: Introductionmentioning
confidence: 99%
“…Notably, various previous studies have consistently reported elevated levels of phenolic compounds within symptomatic spots caused by various pathogens, such as Colletotrichum spp. [16], Pyrenophora tritici-repentis race 1 [32], Gloeosporium spp., Penicillium expansum, Monilinia fructigena [33], Glomerella cingulata [34], and Phytophthora cinnamomi [35].…”
Section: Total Phenolsmentioning
confidence: 99%
“…Among these stressors, Phytophthora cinnamomi Rands is considered the main pathogen responsible for the oak decline. In addition, the effects of climate change, with increasing periods of drought, aggravate the pathology caused by P. cinnamomi , and survival of this agroforestry system is becoming a challenge ( Morcillo et al., 2022 ).…”
Section: Introductionmentioning
confidence: 99%